Alexithymia and its Relationship with Neuroticism among a Sample of Students at Science College in Tishreen University (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to discovering the relation between alexithymia and neuroticism in a Sample of  students in Science College at Tishreen University. It aimed to recognizing differences of alexithymia degree among them due to both sex and age variables . And the level of this variable. The alexithymia scale and Willoughby scale are applied to (258) students for the academic year ( 2017- 2018) divided on (182) less of 22 year and (76) more than (22) year . The following statistical methods were used: percent, means, T – Test, and Pearson correlation.. The results showed significant differences between male and female students of alexithymia degree in favour of the male, thus significant differences were found between first year students and high studies students of alexithymia degree in favour of the first year students. The variance analysis highlighted the increasing of the neuroticism by increasing of alexithymia degree. Where significant differences appeared in neuroticism feature among a group of  low and the middle, the low and the high, the middle and the high alexithymia.